2017
DOI: 10.1515/popore-2017-0025
|View full text |Cite
|
Sign up to set email alerts
|

Algal pigments in Hornsund (Svalbard) sediments as biomarkers of Arctic productivity and environmental conditions

Abstract: Pigments (chloropigments-a and carotenoids) in sediments and macroalgae samples, collected in Hornsund, in July 2015 and July 2016, were analysed (HPLC) in this work. In spite of the aerobic conditions and the periodic intensive solar irradiation in the Arctic environment, neither of which favour pigment preservation in water column and surface sediments, our results indicate that these compounds can provide information about phytoplankton composition, primary production and environmental conditions in this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Here, evidence from the pyloric caeca index at and north of the polar front suggests that a higher quantity and/ or quality of food has been available to the populations recently under the edge of the ice margin, and subsequently stored excess energy (McClintock, 1989). This corresponds to the higher total organic carbon content of the sediment, which is mostly derived from ice algae within the region of study (Stevenson and Abbott, 2019), and evidence of increasing chlorophyll a found in sediments north of the polar front (Krajewska et al, 2017;Morata and Renaud, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Here, evidence from the pyloric caeca index at and north of the polar front suggests that a higher quantity and/ or quality of food has been available to the populations recently under the edge of the ice margin, and subsequently stored excess energy (McClintock, 1989). This corresponds to the higher total organic carbon content of the sediment, which is mostly derived from ice algae within the region of study (Stevenson and Abbott, 2019), and evidence of increasing chlorophyll a found in sediments north of the polar front (Krajewska et al, 2017;Morata and Renaud, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The fact that other studies already detected D+D (Repeta 1989, Brotas and Plante‐Cuny 2003, Krajeswka et al. 2017) and prasinoxanthin in sediments (Sampere et al. 2011, Kang et al.…”
Section: Resultsmentioning
confidence: 94%
“…Increased discharge of freshwater (McClelland et al, 2006) and terrestrial organic matter into Arctic coastal water (Parmentier et al, 2017) further influence the timing of natural cycles. The ecological consequences of these changes manifest in adjusted primary productivity cycles (Lewis et al, 2020), alterations in the quality and quantity of organic matter reaching the seafloor (Krajewska et al, 2017;Stevenson and Abbott 2019;Olivier et al, 2020), benthic biogeochemical cycles (MacDonald et al, 2015;Solan et al, 2020) and the food-web (Yunda-Guarin et al, 2020). Mechanistic understanding of these processes requires continual revision, and in this research topic, we report new findings and emerging insights about how Arctic biogeochemical processes are responding to climate change and altering system dynamics.…”
Section: Introductionmentioning
confidence: 85%